PERAN PENDIDIKAN, DISIPLIN KERJA, DAN FAKTOR LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Ningsih, Anisatul Fitria; Soeliha, Siti; Ciptasari, Ayu Dita Windra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This study aims to analyze and examine the influence of education, work discipline, and work environment on the performance of village officials through job satisfaction. The population of this study consists of village officials from Banyuputih, Sumberejo, and Sumberwaru. The sampling technique used is quota sampling. Data analysis and hypothesis testing are conducted using Structural Equation Modeling - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis testing using the Smart PLS 3.0 application indicate that education does not have a significant effect on job satisfaction and performance. Work discipline has a significant effect on job satisfaction and performance. The work environment does not have a significant effect on job satisfaction and performance. Additionally, job satisfaction does not significantly affect performance. The results of the indirect influence hypothesis testing show that education on job satisfaction through performance has a positive but not significant effect. Work discipline on job satisfaction through performance also has a positive but not significant effect. Similarly, the work environment on job satisfaction through performance has a positive but not significant effect.